p53 Down-Regulates CHK1 through p21 and the Retinoblastoma Protein - Gottifredi, Vanesa (American Society for Microbiology, 2001)
Both fission yeast and mammalian cells require the function of the checkpoint kinase CHK1 for G(2) arrest after DNA damage. The tumor suppressor p53, a well-studied stress response factor, has also been shown to play a role in DNA damage G(2) arrest, although in a manner that is probably independent of CHK1. p53, however, can be phosphorylated and regulated by both CHK1 as well as another checkpoint kinase, hCds1 (also called CHK2). It was therefore of interest to determine whether reciprocally, p53 affects either CHK1 or CHK2. We found that induction of p53 either by diverse stress signals or ectopically using a tetracycline-regulated promoter causes a marked reduction in CHK1 protein levels. CHK1 downregulation by p53 occurs as a result of reduced CHK1 RNA accumulation, indicating that repression occurs at the level of transcription. Repression of CHK1 by p53 requires p21, since p21 alone is sufficient for this to occur and cells lacking p21 cannot downregulate CHK1. Interestingly, pRB is also required for CHK1 downregulation, suggesting the possible involvement of E2F-dependent transcription in the regulation of CHK1. Our results identify a new repression target of p53 and suggest that p53 and CHK1 play interdependent and complementary roles in regulating both the arrest and resumption of G(2) after DNA damage.